Brief behavioral treatment for patients with treatment-resistant insomnia - Wang J; Wei Q; wu X; Zhong Z; Li G (Neuropsychiatric Disease and Treatment)
Jihui Wang, Qinling Wei, Xiaoli Wu, Zhiyong Zhong, Guanying Li Department of Psychiatry, The Third Affiliated Hospital of Sun-Yat Sen University, Guangzhou, Guangdong, People’s Republic of China Objective: To evaluate the efficacy of brief behavioral treatment for insomnia (BBTI) in treating patients with treatment-resistant insomnia.Methods: Seventy-nine adults with treatment-resistant insomnia were randomly assigned to receive either individualized BBTI (delivered in two in-person sessions and two telephone “booster” sessions, n=40) or sleep hygiene education (n=39). The primary outcome was subjective (sleep diary) measures of self-report symptoms and questionnaire measures of Pittsburgh sleep quality index (PSQI), insomnia severity index (ISI), Epworth sleeping scale (ESS), and dysfunctional beliefs and attitudes about sleep scale (DBAS).Results: The repeated-measures analysis of variance showed significant time effects between pretreatment and posttreatment in the scale ratings of PSQI, ESS, DBAS, ISI, sleep latency (SL), time in bed (TIB), sleep efficiency (SE), and wake after sleep onset (WASO) in both groups and group × time interaction (FPSQI =3.893, FESS =4.500, FDBAS =5.530, FISI =15.070, FSL =8.909, FTIB =7.895, FSE =2.926, and FWASO =2.595). The results indicated significant differences between BBTI and sleep hygiene in change scores of PSQI, ESS, DBAS, ISI, SL, TIB, SE, and WASO. Effect sizes were moderate to large.Conclusion: BBTI is a simple and efficacious intervention for chronic insomnia in adults. Keywords: brief behavioral treatment, treatment-resistant, insomnia